Integrating scRNA-seq and bulk RNA-seq to explore the differentiation mechanism of human nail stem cells mediated by onychofibroblasts - Fang, Xia; Zhou, Jiateng; Yang, Yating; Li, Dawei; Wang, Bin (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Nail stem cell (NSC) differentiation plays a vital role in maintaining nail homeostasis and facilitating digit regeneration. Recently, onychofibroblasts (OFs), specialized mesenchymal cells beneath the nail matrix, have emerged as potential regulators of NSC differentiation. However, limited understanding of OFs’ cellular properties and transcriptomic profiles hinders our comprehension of their role. This study aims to characterize human OFs and investigate their involvement in NSC differentiation. Methods: Human OFs were isolated and characterized for their mesenchymal stem cell (MSC)-like phenotype through flow cytometry and multilineage differentiation assays. Bulk RNA-seq analysis was conducted on three samples of OFs and control fibroblasts from human nail units to delineate their molecular features. Integrated analysis with scRNA-seq data was performed to identify key signaling pathways involved in OF-induced NSC differentiation. Co-culture experiments, siRNA transfection, RT-qPCR, and immunocytochemistry were employed to investigate the effect of OF-derived soluble proteins on NSC differentiation. Drug treatments, RT-qPCR, western blotting, and immunocytochemistry were used to verify the regulation of candidate signaling pathways on NSC differentiation in vitro. Results: Human OFs exhibited slow cell cycle kinetics, expressed typical MSC markers, and demonstrated multilineage differentiation potential. Bulk RNA-seq analysis revealed differential gene expression in OFs compared to control fibroblasts, highlighting their role in coordinating nail development. Integrated analysis identified BMP4 as a pivotal signal for OFs to participate in NSC differentiation through mesenchymal-epithelial interactions, with the TGF-beta pathway possibly mediating this signal. OFs synthesized and secreted more BMP4 than control fibroblasts, and BMP4 derived from OFs induced NSC differentiation in a co-culture model. Recombinant human BMP4 activated the TGF-beta pathway in NSCs, leading to cell differentiation, while the BMP type I receptor inhibitor LDN193189 attenuated this effect. Discussion: This study characterizes the cellular and molecular features of human OFs, demonstrating their ability to regulate NSC differentiation via the TGF-beta signaling pathway. These findings establish a connection between the dermal microenvironment and NSC differentiation, suggesting the potential of OFs, in conjunction with NSCs, for developing novel therapies targeting nail and digit defects, even severe limb amputation.